2011
DOI: 10.2147/ahmt.s23649
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for delaying or engaging in early sexual initiation among adolescents in Nigeria

Abstract: BackgroundAnnually, over 1 million births in Nigeria are to teenage mothers. Many of these pregnancies are unwanted and these mothers are also exposed to the risk of human immunodeficiency virus (HIV) infection. Sexual abstinence is a critical preventative health strategy. Several quantitative studies in Nigeria have identified the correlates and determinants of early sex, yet few have explored in depth the underlying reasons for early sex. This paper explores both the key factors that motivate some unmarried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
2
22
0
1
Order By: Relevance
“…The students gave reasons for engaging in their first sexual intercourse and the most common reason was being in love, followed by sexual desire and pressure from partner. A qualitative study using focus group discussion done in four states in Nigeria also showed peer pressure, sex for gift/cash/favour, coercion includes rape as reasons why adolescents engaged in their first sexual experience [4]. Our study shows that 6.5% of the students reported rape as a reason for the first episode of sex.…”
Section: Citation: Chihurumnanya a Lawrence Uo Benedict Na Uche Dmentioning
confidence: 50%
See 2 more Smart Citations
“…The students gave reasons for engaging in their first sexual intercourse and the most common reason was being in love, followed by sexual desire and pressure from partner. A qualitative study using focus group discussion done in four states in Nigeria also showed peer pressure, sex for gift/cash/favour, coercion includes rape as reasons why adolescents engaged in their first sexual experience [4]. Our study shows that 6.5% of the students reported rape as a reason for the first episode of sex.…”
Section: Citation: Chihurumnanya a Lawrence Uo Benedict Na Uche Dmentioning
confidence: 50%
“…Elsewhere in Africa, the prevalence of premarital sex was found to be 32% among the young [3]. In 2008, 20% of women in Nigeria were already sexually active by age 15, and the median age for first sex stood at 17.7 years for women and 20.6 years for men [4]. Another study in South West Nigeria reported premarital sex prevalence of 28.3% among adolescents [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En otro estudio llevado a cabo en Estados Unidos el 25% de los jóvenes encuestados, tanto hombres como mujeres reportaron haber tenido relaciones sexuales a cambio de drogas (Friedman et al, 2008). Al comparar el grupo que inició temprano de RSC con esta práctica, los resultados muestran que hay asociación inversa entre ellos, coincidiendo con lo encontrado por Ankomah et al, (2011) (2016), quienes reportan también cifras más altas, ya que entre 60% a 80% de los estudiantes universitarios en Estados Unidos llevan a cabo sexo casual. Respecto a las posibles causas mencionan García y colaboradores (2012) que se debe a que en la actualidad llevar a cabo sexo casual es una norma cultural entre los jóvenes, que además se asocia con el inicio temprano de relaciones sexuales a corta edad y donde la causa o razón está relacionada también con la permisividad y la falta de lazos afectivos para llevar a cabo encuentros erótico-sexuales que cada vez son más frecuentes en hombres y mujeres.…”
Section: Discussionunclassified
“…This is probably due to the fact that they spent much of their time roaming around the community, an as a consequence they get involved in risky behaviours such as sex. Moreover, they spent more time viewing of locally produced movies, peer pressure, and involvement in transactional sex, whereby girls exchange sex for gifts, cash or other favours (Ankomah et al, 2011). For instance, 60% of girls and 53% of boys had experienced their sexual debut by the age of 18 (Limaye et al, 2012).…”
Section: Discussionmentioning
confidence: 99%